Analisis Perlakuan Terhadap Selisih Kurs Dan Transaksi Mata Uang Asing Pada PT Triputra Agro Persada Tbk (TAPG) (International Forum of Researchers and Lecturers, 2024)
This research aims to conduct research on the company PT Triputra Agro Persada Tbk (TAPG) regarding analysis of the treatment of exchange rate differences and foreign currency transactions. PT TAPG Tbk is involved in complex foreign currency transactions, including the treatment of exchange rate differences that affect the company's financial condition. This study used qualitative research methods. The method applied in collecting information and data in this research is literature study, which involves analysis of journals and books as well as related references to support the research being carried out. This research uses the PT TAPG Tbk Q1 2023 Financial Report as well as a news article from Beritasatu.com entitled “Jaga Arus kas, Triputra Agro Percepat Pembayaran Utang” as data sources. The results of this research indicate that PT TAPG Tbk can minimize the risk of changes in foreign exchange rates and provide further understanding of the complex relationship between currency exchange rates and CPO selling prices as well as risk management in company operations.